Significant Effects of Body Image on Sexual Functions and Satisfaction in Psoriasis Patients - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
Negative body image appraisals may effect the sexual functions, avoidance, and level of finding oneself sexually attractive. The aim of the study is to assess the levels of sexual dysfunction and sexual satisfaction in patients with psoriasis and the effect of the body image appraisal on sexual functions and satisfaction. In all, 216 individuals were included in the study, and 112 of them had psoriasis; 104 individuals who never experienced any skin problems participated in the study and answered questions that assess depression and anxiety levels, sexual problems and satisfaction, as well as body image appraisal. Psoriasis patients showed significantly higher levels of sexual impairments and less satisfaction with sexual life compared to controls. The psoriasis group had lower body image satisfaction compared to the controls. Depression and anxiety levels in the psoriasis group were higher than in the control group. The cognitive meaning of skin involvement as body image satisfaction was found to be the most significant risk factor that affected sexual functions in psoriasis patients. It also predicted sexual satisfaction in the patient group. However, the objective measure of the severity of the disease as Psoriasis Area and Severity Index (PASI) was not a determinant of sexual dysfunctions and satisfaction.
Keywords: QUALITY-OF-LIFE; ERECTILE DYSFUNCTION; IMPACT; INDEX